Wage inequality in Germany after the minimum wage introduction - Thorsten Schank; Mario Bossler (ZBW - Leibniz Information Centre for Economics, 2020)
While monthly wage inequality in Germany continued to increase strongly until 2010, it recently returned to the level of the year 2000. We assess the role of the national minimum wage introduced in 2015. Unconditional quantile regressions combined with difference-indifferences show significant minimum wage effects of varying magnitudes along the lower half of the wage distribution. Employment dynamics cannot explain the effects along the wage distribution, implying strong wage increases among the existing workforce. Wage increases are not offset by decreasing social benefits. Overall, the minimum wage introduction can account for about half of the recent decrease in wage inequality
Keywords: J31; J38; 330; minimum wage; inequality; wages; Germany